Islamic financial culture: alternative economic system for rapid and sustainable economic growth in West African countries (2011)
West African countries are wealthy countries with abundance of both human and natural resources. Some of its member countries are leading member of the OPEC countries. Surprisingly poverty in West African countries is at an alarming rate. Most of its countries are categorized as underdeveloped countries with highest rate of corruption in the world. It is characterized by very weak economies and very low growth rates. There is prevalence of abject poverty as a result of poor economic managements. They have unstable national currencies which are ever losing value and the masses of their rich country live below the poverty line according to UN classification. This study therefore attempts to unravel ways to employing Islamic financial system as an alternative economic system for rapid and sustainable economic growths in West African countries. The study highlights how Islamic money culture, Islamic financial engineering and other Islamic mechanisms such as the gold payment system, Sukuk, Waqf and Zakah systems can become tools in solving the poverty-ridden conditions of West African countries and their teeming populations. Empirical evidence from Malaysian Sukuk forward rates and inflations revealed that Sukuk forward profit rates have positive effects on real economic growth and have the likelihood to keep inflation at its low.